Policy professionals in civil society organizations: Organizational hypocrisy and the myth of member centrality (Sociologisk Forskning, 2023)
Drawing on 24 interviews with policy professionals in 10 Swedish member-based civil society organizations (CSOs), and observations of policy professionals in three of these, we investigate CSOs from the perspective of their policy teams. This paper theoretically addresses how policy professionals relate to the members in whose name they work. This article extends the literature on civil society professionalization by conceptualizing the conflicts pertaining to policy professionals’ work in CSOs and ways of managing these conflicts. We argue that, ordinarily, CSO policy professionals working to influence public policy respond to conflicting logics and myth-like institutional demands for strong and direct influence of member interests by maintaining face and investing in the myth of member centrality. Based on how policy professionals address these issues, we suggest that organizations respond to conflicting institutional pressures and myths via decoupling strategies, discreetly avoiding member concerns while investing in the membership myth, ultimately fostering organizational hypocrisy. Conceptually, the paper contributes by connecting the literatures of civil society professionalization and new institutional theory to the burgeoning literature on policy professionals.
Keywords: civil society; policy professionals; member; myth; organizational hypocrisy